FIRST BREEDING RECORD OF JAVAN MUNIA (Lonchura leucogastroides) IN SUMATRA, INDONESIA - Iqbal, Muhammad; Setiawan, Doni; Setiawan, Arum (BIOVALENTIA: Biological Research Journal, 2015)
Javan Munia (Lonchura leucogastroides) is recently common bird species in southern Sumatra, but no breeding record reported in Sumatra. On 11 October 2015, an active nest of Javan Munia and few juveniles were seen among bunches of Banana (Musa sp) fruits in Sukarejo village, Musi Rawas district, South Sumatra province. This observation is constitute first record of Javan Munia in Sumatra.Â Keywords: First, observation, nest, Javan Munia, Sumatra.